Simulation and Performance Evaluation of Shunt Hybrid Power Filter for Power Quality Improvement Using PQ Theory - R. Balasubramanian; S. Palani (Institute of Advanced Engineering and Science, 2016)
This work proposes the design of shunt hybrid filter using instantaneous power theory to improve the power quality and simulation has been carried out for 3 phase distribution system feeding different types of non linear loads. The proposed filter consists of parallel combination of 5th and 7th tuned selective harmonic elimination passive filters, which is connected in series with a small rating IGBTs based voltage source inverter. In this work, principle of compensation and filtering behavior of the system has been discussed in detail. Instantaneous real and reactive power theory based controller has been designed to estimate the reference current from the distorted current. In order to reduce the harmonics, generated reference currents are tracked by voltage source inverter using hysteresis band current controller. The performance of the hybrid scheme is evaluated for various nonlinear loads using Matlab/ Simulink tool. The detailed analysis has been carried out on harmonics reduction and DC bus voltage regulation and the simulation result ensures the feasibility of suggested control strategy. The proposed topology improves the filtering performance of the passive filter in hybrid scheme.